Mechanical properties and microscopic research of different types of bentonite in conjunction with cement and fine sand - Feng, Zheyuan; Zhang, Zhibo; Tang, Qiang; Zhou, Yu (Soils and Foundations, 2025)
This study delves into the mechanical properties and mechanisms of bentonite-modified cement soil, a reinforced material formed through the physicochemical reactions of cement, soil, and water. Recognizing the material’s widespread application in foundation treatment, slope reinforcement, and seepage control, alongside the environmental pressures of cement production, this research explores the potential of bentonite as a partial cement substitute. Through indoor unconfined compressive strength and permeability tests, varied by curing age, bentonite type, and mix ratio, the study assesses the impact of these factors on the material’s performance. Microscopic analyses further elucidate the intrinsic mechanisms at play. Key findings include: a non-linear relationship between bentonite content and modified cement soil strength, with sodium-based bentonite enhancing strength more effectively than calcium-based; a significant reduction in permeability coefficient with increased bentonite content, particularly with sodium-based bentonite; and a detailed examination of the material’s microstructure, revealing the critical role of cement and bentonite content in pore reduction and strength enhancement. The study underscores the paramount influence of cement content on both strength and permeability, proposing a prioritized framework for optimizing modified cement soil’s performance.